Synchronous triple primary lung cancer with three different histological subtypes in the same lobe: A case report. Issue 5 (20th January 2021) - Koyama, Tsutomu; Shimizu, Kimihiro; Uehara, Takeshi; Matsuoka, Shunichiro; Takeda, Tetsu; Yamada, Kyoko; Eguchi, Takashi; Hamanaka, Kazutoshi; Sano, Kenji
Abstract : Although the number of patients diagnosed with synchronous multiple primary lung cancer is growing because of increased screening and improved imaging technology, synchronous triple primary lung cancer with different histological tumor subtypes occurring in the same lobe of the lung is extremely rare. In this report, we encountered a 64‐year‐old male patient with three different types of nodule in the right lower lobe of the lung found on chest computed tomography (CT) scan. We believed that the patient had triple primary lung cancer, and subsequently performed a right lower lobectomy using video‐assisted thoracoscopic surgery (VATS). The pathological diagnosis was the same as the presurgical diagnosis, but all the nodules were different histological subtypes. To the best of our knowledge, this is the first case reported in the literature of synchronous triple primary lung cancer with three different histological subtypes in the same lobe of the lung. Key points: Significant findings of the study: This is the first case of synchronous triple primary lung cancer with three different histological subtypes in each tumor in the same lobe of the lung. What this study adds: We report the details of the case with immunohistochemical and gene mutation findings, and a literature review of synchronous primary lung cancer. Abstract : This is the first case of synchronous triple primary lung cancer with different histological subtypes in the same lobe of the lung.